2021
DOI: 10.1088/1742-6596/1748/2/022028
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of the Number of Torque Converter Blades on Working Performance Based on the Response Surface Method

Abstract: To understand the effect of the number of torque converter blades on the performance of torque converters, in this paper, we employed computational fluid dynamics and the response surface method to optimize the design of the torque converter. The number of pump blades, stator blades and turbine blades were used as design variables, and the torque transmission ratio and pump capacity factor were used as objective functions for multi-factor optimization design. The results show that the number of turbine blades … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Under the same conditions as the experiment, the torque of the pump, turbine, and stator can be obtained by simulation. Besides, these performance metrics were always used to evaluate the basic cavitation performance of the torque converter [1,24], including torque ratio, efficiency, and capacity constant, which are defined as, 5 2…”
Section: Validation Of Cfd Modelmentioning
confidence: 99%
“…Under the same conditions as the experiment, the torque of the pump, turbine, and stator can be obtained by simulation. Besides, these performance metrics were always used to evaluate the basic cavitation performance of the torque converter [1,24], including torque ratio, efficiency, and capacity constant, which are defined as, 5 2…”
Section: Validation Of Cfd Modelmentioning
confidence: 99%
“…These bubbles then flow to an area of higher pressure, where their volume decreases and they burst. Cavitation can cause damage to the internal flow field of the torque converter, resulting in a decrease in the impeller's torque transmission capacity [3]. This can negatively impact the performance of the torque converter and even lead to damage to the metal structure, as well as the occurrence of vibration and noise [4].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kesy et al [1] used 16 structural parameters, including the inlet and outlet angles of the HTC blades, as design variables to carry out multi-objective optimization design for the cascade system. Xiong et al [2] used the surrogate model method to optimize the design of the HTC by considering the number of pump, stator, and turbine blades as design variables and the torque ratio and pump capacity factor as optimization goals. The results showed that the number of pump blades and stator blades had a significant effect on the performance of the converter, while the number of turbine blades had little influence.…”
Section: Introductionmentioning
confidence: 99%